Assessment of Prescribing Pattern and Safety Profile of Drugs Used in Intranasal Route in Paediatric Age Group of Patients in a Tertiary Care Hospital - Bhadury, A.; Roy, U. K.; Ghosh, T.; Barman, D.; Mandal, P. (Kathmandu University Medical Journal, 2021)
Background Recently there has been an increased preference for intranasal delivery of drugs due to highly vascular nasal mucosa, bypassing first pass metabolism and the blood brain barrier (BBB) lead in quick drug absorption to the systemic circulation and direct access to brain from olfactory region. For pediatric patients this route offers significant benefits over injections or oral routes, like increased compliance, easy administration, and minimal side effects. Objective Assessment of prescription pattern of drugs and safety profile of drugs used by intranasal route in paediatric age group. Method Our study was a prospective observational study paediatric age group of patients conducted in the departments of Pharmacology, Paediatrics and Otorhinolaryngology of Burdwan Medical College and Hospital, Burdwan. Data were collected in CRF and frequency distribution of collected data done. Microsoft Excel 2010 was used for analysis. Result Common age group was infants. Males were more in number. Most common indication was epistaxis. Intranasal drugs per prescription were 1.05. Most commonly prescribed intranasal drug was nasal saline. Nasal decongestant was the most common prescribed medication. Nasal drops were the most common dose formulation. Conclusion Intranasal drug prescribing in our study was mainly aimed for treating local problems, very few being for systemic action. Some prescribing indicators like prescribing by generic name and prescribing from national essential drug lists were acceptable with scope for improvement. Average number of drugs per prescription and antibiotic use was high. Adverse events after intranasal drug use were primarily local and nose related.